The role of the endocannabinoid system in eating disorders: pharmacological implications - Marco, Eva-María; Romero-Zerbo, Silvana Yanina; Paz Viveros, María; Bermúdez Silva, Francisco Javier (Wolters Kluwer Health, 2012)
The endocannabinoid (eCB) system is a widespread intercellular signalling mechanism that plays a critical role in body homoeostasis. It is located in key points involved in food intake and energy expenditure, coordinating all the players involved in energy balance. As such, it has come to be seen as an interesting target for the management of diseases characterized by an imbalanced energy homoeostasis, such as obesity and eating disorders. The aetiology of eating disorders and the molecular systems involved are still largely a mystery. Research has focused on brain circuits where the eCB system plays an important role, such as those related to feeding behaviour and the rewarding properties of food. Accordingly, recent findings have suggested a deregulation of the eCB system in eating disorders. At present, cannabinoid agonists are safe and effective tools in the management of diseases in which weight gain is needed, for example cachexia in AIDS patients. However, studies on the potential therapeutic validity of cannabinoids in eating disorders are scarce and inconclusive. Taken together, all these considerations warrant more preclinical and clinical investigations in the role of the eCB system in eating disorders. Eventually, they may provide novel pharmacological approaches for the treatment of these diseases.
Keywords: Anorexia nerviosa; Bulimia; CB1R; Anandamide; Anorexia nervosa; Binge eating; Bulimia nervosa; Endocannabinoid-based therapy; Endocannabinoids